Effect of dual-stage ageing and RRA treatment on the three-body abrasive wear of the AW7075 alloy - Lachowicz, Marzena M. (Strojniški vestnik, 2022)
The paper presents an analysis of the influence of the heat treatment state on the abrasive wear of the AW7075 aluminium alloy. To determine the hardening state, the material hardness was measured. It was found that hardness is not the only factor that influences this type of wear. For this reason, the influence of the emerging microstructure is also analysed in the considerations. After tribological tests, microscopic observations of surface features were carried out to determine the dominant mechanisms of surface damage. The results were extended by the hardness distribution carried out on the cross-section. There were no changes in hardness that could be related to either strain hardening or structural changes caused by friction.
Keywords: abrasive wear; abrazivna obraba; aluminijeve zlitine; aluminum alloys; AW7075; hardness; heat treatment; microstructure; mikrostrukture; trdota